Diagnostic And Treatment Tactics in Gastroesophageal Reflux Disease (Texas Journal of Medical Science, 2022)
This article analyzes the diagnostic and therapeutic tactics of treating 234 patients with gastroesophageal reflux disease and complicated with various erosive pathologies of the esophageal mucosa, which were investigated in the diagnostic departments of the Samarkand City Medical Association and the State Institution “Republican Specialized Center of Surgery named after academician V. Vakhidov" in the period 2019-2020. Patients, according to indications, were examined in different modes of endoscopic examination (in the usual and in the narrow-spectrum mode (NBI mode).